Growth Performance of Nursery Pigs in the Immediate Post-Weaning Period According to Different Vaccination Strategies - M. B. Menegat; L. L. Thomas; M. D. Tokach; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2018)
The objective of this study was to evaluate the growth performance of nursery pigs immediately after weaning based on different vaccination strategies. A total of 300 weaned pigs (DNA 241 × 600, DNA Genetics, Columbus, NE) with an initial body weight (BW) of 14.0 lb and approximately 21 d of age were used in this trial. Pigs were allotted to pens in a completely randomized design with 5 pigs per pen and a total of 60 pens. All pigs received one dose of a commercial combination vaccine for Porcine Circovirus Type 2 andMycoplasma hyopneumoniaeat approximately d 7 of age. At weaning, 30 of the 60 pens of pigs were randomly selected to receive the second dose of the vaccine. Pigs were fed common diets based on corn and soybean meal. Pigs were weighed and feed disappearance was recorded on d 0, 2, 4, 6, and 8 to determine average daily gain (ADG), average daily feed intake (ADFI), and feed-to-gain ratio (F/G). The results of this study demonstrate no evidence (P>0.05) of difference for the effect of vaccination or interaction between vaccination and day on growth performance after weaning. However, there was evidence (P<0.0001) for an effect of day on BW, ADG, ADFI, and F/G. In the first 2 d after weaning, pigs consumed nearly no feed and, consequently, lost weight (P<0.0001). In the following days, pigs gradually increased feed intake and gained weight from d 2 to 4 (P<0.0001), but lost weight from d 4 to 6 (P<0.0001). A significant increase (P<0.0001) in feed intake and weight gain was observed from d 6 to 8 after weaning, resulting in an increase in BW. In conclusion, weanling pigs have a slow start on feed and low growth performance during the first week after weaning, but rapidly increase feed intake and weight gain toward the end during the end of the first week of nursery. Vaccination at the moment of weaning was not an aggravating factor to post-weaning growth performance in this study.
Keywords: growth; post-weaning; vaccination; weanling pig